Critical thinking skills, 7e learning cycle model, science of elementary school - Inggit Septianingrum; Suharno Suharno; Anesa Surya (Didaktika Dwija Indria, 2019)
This study aimed to improve student’s critical thinking skills in water cycle material and human activities that influence it by applying the learning cycle model 7e. This research is a Classroom Action Research (CAR) conducted for two cycles. The research subjects were fifth grade students of SD N Pajang II Surakarta in 2018/2019 which amounted to 24 students. Data collection techniques consist of observation, interviews, tests and documentation. The validity test using triangulation. While the analysis of this research data uses an interactive data analysis model by Miles-Huberman. The initial conditions indicate that students' critical thinking skills are 8.34% classically. The results obtained from the first cycle of action in the first learning were 21.74% classically, the second learning increased to 30.44% classically, and the third lesson increased to 40.91% classically. The study continued to the second cycle in the first learning increased to 56.53%, the second learning increased to 77.27% classically, and the third learning had reached 86.96% classically.